Estudo da sedimentação em suspensões de fluidos com características reológicas pseudoplásticas - Moreira, Bruno Arantes (2014)
Understanding the behavior of a suspension settling in fluids with shear thinning characteristics has been a subject of great interest in many industrial operations, such as in the exploratory processes of oil and gas. However, despite the importance of the topic, it appears that several quantitative information about the phenomenon have not yet been satisfactorily empirically documented. In this context, this study aimed to obtain new information about the interaction and dynamics of a group of particles settling in fluids with similar rheological behavior to those used in well drillings (shear thinning fluids). For this purpose, the y-ray attenuation technique was used, allowing the solids concentration monitoring for different positions of the recipient along the time. This technique enabled the realization of indirect measurements even in high concentrations of solids. In this work, were also proposed constitutive equations for the pressure on the solids P(Es) and permeability of porous medium k(Es) for suspensions consisting of bridging agents, which are commonly added to drilling fluids. The constitutive relations are intended to assist in the modeling and simulation of the phenomena related to filtration with filter cake formation for the static conditions. The results of this study showed that the memory effects when present in shear thinning fluids, have a significant influence in the rates of particles settling. For the shear thinning fluid, it was also found that the sediment formation was initially faster, when compared with the newtonian fluid which had similar apparent viscosity. However, the final compaction of the sediment in the non-newtonian fluid required a longer period. Overall, this study provided relevant information for the gravitational sedimentation in non-newtonian fluids, covering this way, a subject in the literature that several issue remains to be explored and better understood.